Short Intracellular HIV-1 Transcripts as Biomarkers of Residual Immune Activation in Patients on Antiretroviral Therapy - Ishizaka, Aya (J Virol, 2016)
HIV-1 patients continue to remain at an abnormal immune status despite prolonged combination antiretroviral therapy (cART), which results in an increased risk of non-AIDS-related diseases. Given the growing recognition of the importance of understanding and controlling the residual virus in patients, additional virological markers to monitor infected cells are required. However, viral replication in circulating cells is much poorer than that in lymph nodes, which results in the absence of markers to distinguish these cells from uninfected cells in the blood. In this study, we identified prematurely terminated short HIV-1 transcripts (STs) in peripheral blood mononuclear cells (PBMCs) as an efficient intracellular biomarker to monitor viral activation and immune status in patients with cART-mediated full viral suppression in plasma. STs were detected in PBMCs obtained from both treated and untreated patients. ST levels in untreated patients generally increased with disease progression and decreased after treatment initiation. However, some patients exhibited sustained high levels of ST and low CD4(+) cell counts despite full viral suppression by treatment. The levels of STs strongly reflected chronic immune activation defined by coexpression of HLA-DR and CD38 on CD8(+) T cells, rather than circulating proviral load. These observations represent evidence for a relationship between viral persistence and host immune activation, which in turn results in the suboptimal increase in CD4(+) cells despite suppressive antiretroviral therapy. This cell-based measurement of viral persistence contributes to an improved understanding of the dynamics of viral persistence in cART patients and will guide therapeutic approaches targeting viral reservoirs. IMPORTANCE Combination antiretroviral therapy (cART) suppresses HIV-1 load to below the detectable limit in plasma. However, the virus persists, and patients remain at an abnormal immune status, which results in an increased risk of non-AIDS-related complications. To achieve a functional cure for HIV-1 infection, activities of viral reservoirs must be quantified and monitored. However, latently infected cells are difficult to be monitored. Here, we identified prematurely terminated short HIV-1 transcripts (STs) as an efficient biomarker for monitoring viral activation and immune status in patients with cART-mediated full viral suppression in plasma. This cell-based measurement of viral persistence will contribute to our understanding of the impact of residual virus on chronic immune activation in HIV-1 patients during cART.